2002
DOI: 10.3354/meps230087
|View full text |Cite
|
Sign up to set email alerts
|

Role of decomposition of mangrove and seagrass detritus in sediment carbon and nitrogen cycling in a tropical mangrove forest

Abstract: The elemental composition and in situ decomposition of detritus of Rhizophora apiculata and Enhalus acoroides were studied in mangrove and seagrass bed sediments in the Bangrong mangrove, Phuket, Thailand, and compared with controlled laboratory flux incubations. At the field site detritus was buried in litter-boxes in the sediments and changes in particulate organic carbon and nitrogen in detritus and sediments were followed for up to 2 mo. In the flux incubations the sediments were amended with mangrove and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 50 publications
3
31
2
Order By: Relevance
“…Given that decomposition rates of organic matter are faster when nitrogen and phosphorus content are higher (Enríquez et al, 1993) and that belowground plant parts generally have lower nutrient content than leaves, it is not surprising that decomposition of belowground parts is much slower than that of leaves (Holmer and Olsen, 2002;Fourqurean and Schrlau, 2003), but there are few reports of decay rates of belowground biomass. In Posidonia oceanica, rhizomes decayed at a rate of 0.0001 d −1 and belowground leaf sheaths at a rate of 0.0002 d −1 , which was two orders of magnitude slower than the decomposition of leaves at the same location (Romero et al, 1992).…”
Section: Rates Of Decomposition Of Organic Matter In Tidal Marsh Manmentioning
confidence: 99%
“…Given that decomposition rates of organic matter are faster when nitrogen and phosphorus content are higher (Enríquez et al, 1993) and that belowground plant parts generally have lower nutrient content than leaves, it is not surprising that decomposition of belowground parts is much slower than that of leaves (Holmer and Olsen, 2002;Fourqurean and Schrlau, 2003), but there are few reports of decay rates of belowground biomass. In Posidonia oceanica, rhizomes decayed at a rate of 0.0001 d −1 and belowground leaf sheaths at a rate of 0.0002 d −1 , which was two orders of magnitude slower than the decomposition of leaves at the same location (Romero et al, 1992).…”
Section: Rates Of Decomposition Of Organic Matter In Tidal Marsh Manmentioning
confidence: 99%
“…In addition, seagrass beds get carbon input from nearby coastal systems such as mangrove forests (e.g., Bouillon, Moens, & Dehairs, 2004). Several studies aimed to study the origin of carbon in these systems (e.g., Fleming, Lin, & Sternberg, 1990;Holmer & Bachmann Olsen, 2002;Marguillier, van der Velde, Dehairs, Hemminga, & Rajagopal, 1997) rather than to unravel the effects of total resource availability on consumers.…”
Section: Introductionmentioning
confidence: 99%
“…Despite considerable study, the linkages between mangrove forest detritus and adjacent estuarine water ecosystems are inadequately understood (Odum & Heald 1972, Fell & Master 1973, Snedaker & Lugo 1973, Cundell et al 1979, Twilley et al 1986, Boto 1992, Holmer & Olsen 2002. Proffitt et al (1993) reported that grazing by the intertidal gastropod Melampus coffeus L. (Pulmonata: Ellobiidae) in both field and laboratory trials caused very high rates of breakdown of Rhizophora mangle, Avicennia germinans and Laguncularia racemosa leaves.…”
Section: Introductionmentioning
confidence: 99%